Dengue protease inhibition activity of selected malaysian medicinal herbs - Salleh H.M.; Chong S.-L.; Othman R.; Hazni H.; Ahmad K.; Mohd Yusof M.Y.Z.; Fauzi N.W.; Wahab H.A.; Liew S.Y.; Awang K. (Malaysian Society for Parasitology, 2024)
Indexed by WOS/SCOPUS/ERA